A study of the reactivity of cyclic aminomethylammonium mannich salts. (3rd December 2022) - Dimitrova, Daniela; McMahon, Connor; Kennedy, Alan R.; Parkinson, John A.; Leach, Stuart G.; Boulton, Lee T.; Pascoe, David D.; Murphy, John A.
Abstract: A novel method for the preparation of aminoalkylaminomethyl products was developed utilising novel Mannich-type salts featuring a R2 NCH2 NR3 + moiety. This methodology showed good nucleophile scope and was successfully employed in reactions under basic, acidic, and neutral conditions. A wide range of diamine products was successfully synthesised, including a neuropeptide Y antagonist. Graphical abstract: Image 1